2018
DOI: 10.1016/j.vaccine.2018.09.065
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of African horse sickness virus (AHSV) VP2 based vaccines provides complete clinical protection in a mouse model

Abstract: HighlightsBaculovirus-expressed AHS-VP2 and MVA-VP2 vaccines were evaluated in mice.Clinical protection was complete in mice receiving one or two doses of MVA-VP2.Clinical protection complete after two doses of baculovirus-expressed VP2.Significant reduction of viraemia in all vaccinated groups.Significant levels of immunity were achieved with one dose of either vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In terms of efficacy, baculovirus expressed VP2/VP5 sub‐unit vaccines have been demonstrated to induce virus neutralising antibodies and protection in laboratory rodents and also in horses, 25,26 It is believed that they did not reach the market due to the high costs of manufacturing in an industrial setting. However, recent studies demonstrated that vaccine production yields can be improved significantly and that at least in the mouse model, protection can be achieved with just one vaccine dose 27 . Canarypox‐based vaccines expressing AHSV‐VP2/ VP5 have also shown promising results in horses, at least with AHSV serotype 4, demonstrating both cellular and humoral protective immune responses could be induced 28,29 .…”
Section: Are Ahsv Vaccines Feasible?mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of efficacy, baculovirus expressed VP2/VP5 sub‐unit vaccines have been demonstrated to induce virus neutralising antibodies and protection in laboratory rodents and also in horses, 25,26 It is believed that they did not reach the market due to the high costs of manufacturing in an industrial setting. However, recent studies demonstrated that vaccine production yields can be improved significantly and that at least in the mouse model, protection can be achieved with just one vaccine dose 27 . Canarypox‐based vaccines expressing AHSV‐VP2/ VP5 have also shown promising results in horses, at least with AHSV serotype 4, demonstrating both cellular and humoral protective immune responses could be induced 28,29 .…”
Section: Are Ahsv Vaccines Feasible?mentioning
confidence: 99%
“…However, recent studies demonstrated that vaccine production yields can be improved significantly and that at least in the mouse model, protection can be achieved with just one vaccine dose. 27 Canarypox-based vaccines expressing AHSV-VP2/ VP5 have also shown promising results in horses, at least with AHSV serotype 4, demonstrating both cellular and humoral protective immune responses could be induced. 28,29 Likewise, AHSV-VP2 vaccines based on recombinant modified Vaccinia Ankara virus (MVA) were shown to be protective in small animal models and in horses and it was shown that the main protective mechanism was mediated by virus neutralising antibodies.…”
Section: Are Ah S V Vaccine S Fe a S Ib Le?mentioning
confidence: 99%
“…Of concern, LAVs are associated with reversion to virulence, vector’s transmission, absence of DIVA (Differentiating Infected from Vaccinated Animals) capacity, teratogenicity, and gene reassortment that lead to the establishment of new genetic variants [ 3 , 14 , 15 , 16 , 17 , 18 ]. To address the need for safe and more effective vaccines, several candidates have been evaluated including subunit vaccines, virus like particles (VLPs), avian reovirus muNS protein microspheres (MS), recombinant poxviruses and reverse genetic approaches [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 •• , 29 •• , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 • ] ( Table 1 ).…”
Section: New Approaches In Vaccine Generation Against Ahsvmentioning
confidence: 99%
“…As VP2 is the main target for virus neutralizing antibodies (NAbs) [ 38 , 39 ] that are related with protection [ 40 , 41 , 42 ], several potential vaccines under investigation rely in the induction of VP2 NAbs; however these do not offer full cross-protection among serotypes. Subunit vaccines based on VP2 produced by baculovirus expression system have been analyzed either singly or in combination with VP5 and VP7 inducing protective immunity against homologous AHSV-4 [ 23 , 26 , 31 ]. A multiserotype cocktail of subunit VP2 vaccine (serotypes 2, 4, 5, 6, 9) was tested in guinea pigs eliciting a low cross-neutralizing antibody response for genetically related AHSV-8 [ 32 ].…”
Section: New Approaches In Vaccine Generation Against Ahsvmentioning
confidence: 99%
See 1 more Smart Citation